TEACHER ROLES AND STUDENTS RESPONSES IMPLEMENTED IN A SENIOR HIGH SCHOOL IN SURABAYA - Elda Devin; Josefa J. Mardijono (Institute of Research and Community Outreach - Petra Christian University, 2015)
In this study, the writer would discuss some types of teacher roles which can be implemented in the classroom. The purpose of this study was to find out the types of teacher roles applied in the conversation class and the students responses. The subject of this study was a teacher who teaches a conversation class to senior high school students. The writer used the theories about types of teacher roles by Harmer (2001 and 2007) and Edge&Garton (2007) and students responses by Brown (2007). The writer used classroom observation and video recording to collect the data. In addition, the writer recorded two meeting. The findings revealed that there were six types of teacher roles and five types of students responses applied in this class. The teacher roles are controller, organizer, assessor, resource, observer, and motivator which played based on their functions. The five responses were specific, choral, open-ended, off task, and silence responses. From this study, it could be concluded that the teacher played the five types of teacher roles to engage the active participant from the students shown through the students responses.